Novel Species-Specific Primers Enable Accurate Detection and Quantification of Pseudomonas aeruginosa via qPCR - Chaerin Kim; Ravi Jothi; Kwang-Kyo Oh; Dong Suk Park (Journal of Food Protection)
Pseudomonas aeruginosa, a notable pathogen in nosocomial infections, also emerges as a significant and often underestimated foodborne pathogen, frequently identified in diverse food categories, including meat, milk, fruits, vegetables, and water. Its resilience, virulence, and ability to form biofilms necessitate the development of novel methods for early detection of its presence in food products. This study aims to identify, design, and validate specific genetic markers for P. aeruginosa detection through quantitative PCR (qPCR) analysis. In this study, 816 publicly available genome sequences of P. aeruginosa strains were compared to identify a conserved and specific gene encoding a hypothetical protein (WP_003109295.1) in P. aeruginosa DSM 50071. Primers targeting this gene region were designed and validated for their ability to detect P. aeruginosa using qPCR, demonstrating a high level of sensitivity and specificity for P. aeruginosa among various Pseudomonas species. Further validation through standard curve analysis using three different templates such as cloned DNA, genomic DNA, and cell suspension confirmed the exceptional sensitivity and specificity of the designed primers in quantifying P. aeruginosa via qPCR. Additionally, the on-site application of these primers was validated on P. aeruginosa-inoculated carrot samples, highlighting their reliability and accuracy. The proposed direct qPCR method offers substantial advantages for the rapid, simple, and specific detection of P. aeruginosa, enhancing the efficiency of diagnostic and monitoring processes for this pathogen in food and vegetable distribution systems.